(untitled) (Zaporizhzhia Historical Review, 2021)
The article considers national relations in Crimean village in the 1920s and their influence on the character of the land politic of the Soviet power. It analyzes the national structure of Crimean village before collectivization. The authors comes to a conclusion that unsolved land problem in the Crimean ASSR and the class approach to various social and national groups of peasantry in politics of power bodies led to artificial arousal of class struggle and intensification of national antagonisms in the region.